Effect of Concussions on the Performance of Running Backs and Wide Receivers in the National Football League. Issue 11 (September 2019) - Jildeh, Toufic R.; Okoroha, Kelechi R.; Taylor, Kevin A.; Buckley, Patrick; Mehta, Samir; Mehran, Nima; Moutzouros, Vasilios
Background: Concussion injuries are common in professional football players; however, their effect on player performance remains unclear. Purpose: To quantify the effect of concussions on the performance of running backs and wide receivers in professional football players. Study Design: Cohort study; Level of evidence, 3. Methods: Concussion data from the National Football League were collected for a period of 4 seasons (2012-2015) for running backs and wide receivers. Age, experience, position, time to return to play, yearly total yards, and touchdowns were recorded. A power rating (total yards divided by 10 plus touchdowns multiplied by 6) was calculated for each player's injury season as well as for the 3 seasons before and after their respective injury. A control group of running backs and wide receivers without an identified concussion injury who competed in the 2012 season was assembled for comparison. Player performance up to 3 seasons before and after the injury season was examined to assess acute and longitudinal changes in player performance. Results: A total of 38 eligible running backs and wide receivers sustained a concussion during the study period. Thirty-four (89%) players were able to return to competition in the same season, missing an average of 1.5 ± 0.9 games; the remaining 4 players returned in the subsequent season. Power ratings for concussed players were similar to those of controls throughout the study period. Concussed players did not suffer an individual performance decline upon returning within the same season. Furthermore, no significant difference in change of power rating was observed in concussed players in the acute (±1 year from injury; −1.2 ± 4.8 vs –1.1 ± 3.9, P = .199) or chronic (±3 years from injury; –3.6 ± 8.0 vs –3.0 ± 4.5, P = .219) setting compared with controls. All concussed players successfully returned to competition in either the index or next season. Conclusion: A high rate of National Football League running backs and wide receivers are able to return to play after a concussion injury. These players were found to perform at a similar level in both the acute and long-term period after concussion.